Peningkatan Pengetahuan Siswa SLTA Sederajat Tentang Komputer Melalui Workshop Pengenalan Hardware Komputer - Muhammad Ibrahim Nasution; Yuhefizar; Rasyidah (Politeknik Caltex Riau, 2022)
The purpose of this service activity is to increase knowledge about computers to high school students and equivalent In Lintau Buo, the activity carried out is a workshop on the introduction of computer hardware and software, based on observations of the ability of high school students equivalent around lintau buo about computer equipment is still low, because a workshop on computers was held. The place for the workshop was the Politeknik Negeri Padang, Tanah Datar Campus, the stages of activity starting from Preparation, Implementation and Evaluation. The number of participants in this workshop was 20 people from MAN 3 Tanah Datar, SMAN 1 Lintau Buo, SMKN 1 Lintau Buo and SMAN 2 Lintau Buo. The workshop material provided is an introduction to Hardware Software, Assembling a computer and installing applications on a computer. The impact of this workshop can be seen from the results of the Pretest and Posttest where when the Pretest the average score of the participants is 56.5 after attending the workshop and doing the Posttest the average score of the participants increases to 85.